Energy Efficiency in Industry - Dobrotkova, Zuzana (World Bank, Washington, DC, 2018)
The vast energy efficiency potential in industry remains largely untapped, impairing global efforts to mitigate climate change. With the right steps, energy savings by 2035 could rise to 668 million metric tons of oil equivalent in OECD countries, and up to five times more in developing countries.